The soluble nectin-4 ecto-domain promotes breast cancer induced angiogenesis via endothelial Integrin-β4. (September 2018) - Siddharth, Sumit; Nayak, Anmada; Das, Sarita; Nayak, Deepika; Panda, Jyochanamayi; Wyatt, Michael D.; Kundu, Chanakya Nath
Highlights: Using in vitro, in vivo, In Ovo and Ex vivo model system we have proved that a pvrl-4 encoded gene Nectin-4 has angiogenesis potentiality. Nectin-4 is a potential angiogenesis biomarkers in breast cancer stem cells. Nectin-4 ecto-domain physically interacts with integrin-β4 and activates the angiogenesis pathways. Nectin-4 and integrin-β4 interaction promotes angiogenesis via the Src, PI3K, AKT, iNOS pathway but not by Phospho-Erk or NF-κβ pathways. Abstract: Cancer stem cells secrete diffusible factors into the microenvironment that bind to specific endothelial cell receptors and initiate an angiogenesis cascade. Tumor-induced angiogenesis is an important parameter of tumorigenesis and is critical for tumor growth and metastasis. A pvrl-4 encoded gene, NECTIN-4, has potential roles in cancer cell growth and aggressiveness, and it is only expressed in cancer cells. There is evidence that nectin-4 plays a role in tumorigenesis, but the function of nectin-4 in tumor angiogenesis has lacked thorough evidence of mechanism. Using highly metastatic breast cancer cells and human umbilical vein endothelial cells (HUVECs), we have developed an excellent angiogenesis model and systematically studied the contribution of nectin-4 to angiogenesis. We also provide in-depth in ovo, in vivo and in vivo evidence that nectin-4 causes angiogenesis. Following hypoxia, metastatic breast cancer stem cells (mBCSCs) driven ADAM-17 expression causes the shedding of the ecto-domain of nectin-4 into the microenvironment, which physically interacts with integrin-β4 specifically on endothelial cells. This interaction promotes angiogenesis via the Src, PI3K, AKT, iNOS pathway and not by Phospho-Erk or NF-κβ pathways. In vitro, in ovo and in vivo induction and abrogation of an angiogenesis cascade in the presence and absence of the nectin-4 ecto-domain, respectively, confirms its role in angiogenesis. Thus, disrupting the interaction between nectin-4 ecto-domain and integrin-β4 may provide a means of targeting mBCSC-induced angiogenesis.